Non-volant small mammal diversity assessment in Lata Bijih and Lata Janggut using cage traps - Mohamad Zainudin; Jayaraj V.K (2016)
A recent non-volant mammal survey was conducted at two sites in Kelantan namely Lata Janggut and Lata Bijih. The main objective of this study was to determine the diversity and abundance of non-volant small mammal in both sites. Fifty cage traps used baited with bananas (Musa acuminata). These traps were placed for four days at both sites respectively. In total, 43 individuals of non-volant small mammal were recorded comprising of 10 species, three Orders and four Families namely; Muridae, Erinaceidae Sciuridae, and Tupaiidae. The moonrat (Echinosorex gymnura) captured was a new locality record for the State of Kelantan. Continued surveys are needed because there is a need to record more data on the diversity of small mammal in Kelantan.